If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 33 + -2(4 + -2w) 23 = 33 + (4 * -2 + -2w * -2) 23 = 33 + (-8 + 4w) Combine like terms: 33 + -8 = 25 23 = 25 + 4w Solving 23 = 25 + 4w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4w' to each side of the equation. 23 + -4w = 25 + 4w + -4w Combine like terms: 4w + -4w = 0 23 + -4w = 25 + 0 23 + -4w = 25 Add '-23' to each side of the equation. 23 + -23 + -4w = 25 + -23 Combine like terms: 23 + -23 = 0 0 + -4w = 25 + -23 -4w = 25 + -23 Combine like terms: 25 + -23 = 2 -4w = 2 Divide each side by '-4'. w = -0.5 Simplifying w = -0.5
| 12/11•5/8 | | 12/8•5/8 | | 7(3x-2)=-39 | | -9x+3=-8x | | 9x+8=-1x-13 | | 3+.20y=2x+4 | | (n+18)+2n=90 | | -23=2x+3x+2 | | x/3-3=-2 | | 6(x/6)-6(4)=6(x/6) | | -17x+18=13 | | x-7=1-9 | | -7=5-2n+6n | | a+(a-15)=55 | | -8-n=0 | | 8p+3=3p+13 | | 5n+3=14-5n | | -2x+5-5x=5 | | 68mi/h=mi/sec | | (-14xy^2)/(21y^3)= | | 8x-(3x-11)=36 | | 4y=2x+9solve | | 3b^2+7b-6= | | 0.4x-8=9-0.6x | | -5=6x-4x+1 | | 72+6y=-6y | | 5x^2-2x-365=0 | | 40x+8y=48 | | 4p+7=3p+11 | | (5y-4z)(7y+3z)= | | -6=5x-7x-6 | | 4(-3+x)=5x-0.25 |